Determining the angle of the frontal working surface of the soil-piercing head asymmetrical tip for static soil-piercing - Suponyev, Vladimir; Ragulin, Vitaliy; Oleksyn, Volodymyr; Koval, Oleksandr; Koval, Andrii; Vysokovych, Yevhen; Супонєв, Володимир Миколайович; Рагулін, Віталій Миколайович; Олексин, Володимир Іванович; Коваль, Олександр Олександрович; Коваль, Андрій Борисович; Високович, Євген Вадимович (Харківський національний автомобільно-дорожній університет, 2024)
Problem. From the analysis of the technical literature, it was established that among the trenchless technologies for laying underground engineering communications and service pipelines, the technology with the possibility of forming a horizontally directed communication cavity in the soil using soil-piercing installations of static action is the most common. Goal. This method consists in forcefully pressing a soil-piercing working body, which has the form of a conical-cylindrical projectile, into the soil. At the same time, the well is formed by radial extrusion of the soil around the formed well. However, the use of such equipment does not provide high accuracy, which limits its practical application within 20 m. It is not sufficient for modern requirements of creating transitions during the laying of communications. Methodology. One of the ways to improve the efficiency of laying underground networks is to extend this method over a longer distance by correcting the trajectory of the working body. This is achieved by using a soil-piercing head with an asymmetric tip. Due to this, in addition to the axial resistance of the soil, a transverse component force appears, which deflects the head during its advancement in the soil. The question of determining the angle of displacement of such a tip is important in terms of the process control. Results. In the paper, a calculated dependence is proposed for determining the rational value of the angle of inclination of an asymmetric tip working surface, which is a flat plane cut at the angle of a cylinder. An analysis of the dependence of the angle of the working surface inclination on the physical and mechanical properties of the soil is also given. Originality. It was determined that the maximum angle of inclination of the frontal surface is determined by the conditions of soil descent from it. Its maximum value, for example when working in loam, should not exceed 55o-67o for a tip made of steel. Practical value. The obtained calculated dependence can be useful for determining the angle of inclination of the flat frontal surface of the tip of the soil piercing working tool for controlled static soil piercing at the stage of designing networks and choosing an effective method for drilling a well under roads or other obstacles.
Визначення куту нахилу лобової робочої поверхні асиметричного наконечника грунтопроколюючої головки для статичного проколу ґрунту
Keywords: engineering communications; soil development; trenchless technologies; borehole; static soil puncture; soil compaction; distribution pipeline networks; інженерні комунікації; розробка ґрунтів; безтраншейні технології; свердловина; статичний прокол ґрунту; ущільнення ґрунту; розподільні трубопровідні мережі; 624.132.3; 10.30977/AT.2219-8342.2024.54.0.03